Factors associated with participation and nonparticipation in a VA Whole Health Primary Care Pain Education and Opioid Monitoring Program (PC-POP) - Martinson, PhD, Amber; Kutz, PhD, Amanda; Marchand, MD, William; Carney, RN, Julie; Clinton-Lont, MS, CNP, Jamie (Journal of Opioid Management, 2020)
Objective: As part of the evaluation of the Whole Health Primary Care Pain Education and Opioid Monitoring Program (PC-POP), we compared demographic and health characteristics between participants and nonparticipants drawn from the same defined population. Design/Methods: Retrospective chart review comparing participants and nonparticipants in terms of two categories of variables: (1) demographic characteristics and (2) physical/mental health characteristics. Setting: VA Primary Care. Subjects: Adult veterans with chronic noncancer pain receiving opioid therapy >3 months being managed in primary care. Results: A total of 749 veterans (424 participants in PC-POP and 325 nonparticipants) were included in the final analysis. Results showed that nonparticipation was associated with more widespread musculoskeletal pain, low back pain, anxiety, higher mortality, and rural areas. Participation was associated with more medical diagnoses overall, hypertension, sleep apnea, fibromyalgia, peripheral nerve pain, depression, and female gender. Other demographic and physical/mental health variables did not significantly differ between the groups. Conclusions: Given that primary care is the dominant healthcare setting in which opioids are prescribed for chronic noncancer pain, programs are needed to assist primary care providers to meet the rigorous requirements of guideline concordant care. The current study examined participation factors in such a program and found that certain veterans were less likely to participate than others. Identifying such veterans at the outset, in combination with intentional recruitment efforts and individualized interventions, may promote entry into PC-POP.